Full Waveform Ambient Noise Tomography for East Antarctica ... - Emry, Erica; Hansen, Samantha (U.S. Antarctic Program (USAP) Data Center, 2024)
Recent investigations in polar environments have examined solid-Earth-ice-sheet feedbacks and have emphasized that glacial isostatic adjustment, tectonic, and geothermal forcings exert first-order control on the physical conditions at and below the ice-bed interface and must be taken into account when evaluating ice-sheet evolution. However, the solid-Earth structure beneath much of Antarctica is still poorly constrained given the sparse distribution of seismic stations across the continent and the generally low seismicity rate. One region of particular interest is the Wilkes Subglacial Basin (WSB) in East Antarctica. During the mid-Pliocene warm period, the WSB may have contributed 3-4 m to the estimated 20 m rise in sea-level, indicating that this region could also play an important role in future warming scenarios. However, the WSB may have experienced notable bedrock uplift since the Pliocene; therefore, past geologic inferences of instability may not serve as a simple analogue for the future. Using ...